Oscillatory response of Larsen C Ice Shelf flow to the calving of iceberg A-68 - Katherine A. Deakin; Frazer D. W. Christie; Karla Boxall; Ian C. Willis (Journal of Glaciology)
The collapse of several ice shelves in the Antarctic Peninsula since the late 20th century has resulted in the upstream acceleration of multiple formerly buttressed outlet glaciers, raising questions about the stability of Antarctica's remaining ice shelves and the effects their demise may have upon inland ice. Here, we use high temporal resolution Sentinel-1A/B synthetic aperture radar-derived observations to assess the velocity response of Larsen C Ice Shelf (LCIS) to the calving of colossal iceberg A-68 in 2017. We find marked oscillations in ice-shelf flow across LCIS in the months following A-68's calving, beginning with a near-ice-shelf-wide slowdown of 11.3 m yr−1 on average. While falling close to the limits of detectability, these ice-flow variations appear to have been presaged by similar oscillations in the years prior to A-68's breakaway, associated primarily with major rifting events, together reflecting potentially hitherto unobserved ice-shelf mechanical processes with important implications for ice-shelf weakening. Such ice-flow oscillations were, however, short-lived, with more recent observations suggesting a deceleration below longer-term rates of ice flow. Collectively, our observations reveal complex spatial-temporal patterns of ice-flow variability at LCIS. Similarly abrupt fluctuations may have important implications for the stability of other ice shelves, necessitating the continued, close observation of Antarctica's coastline in the future.